2012
DOI: 10.1128/jvi.05581-11
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Host Age on the Transport of Complement-Bound Complexes to the Spleen and the Pathogenesis of Intravenous Scrapie Infection

Abstract: Infections with variant Creutzfeldt-Jakob disease (vCJD) have almost exclusively occurred in young patients, but the reasons for this age distribution are uncertain. Our data suggest that the pathogenesis of many peripherally acquired transmissible spongiform encephalopathy (TSE) agents is less efficient in aged individuals. Four vCJD cases linked to transfusion of vCJDcontaminated blood or blood products have been described. Three cases occurred in elderly patients, implying that intravenous exposure is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 49 publications
8
65
1
2
Order By: Relevance
“…54 In contrast, it was recently demonstrated that the inability of aged mice to develop transmissible spongiform encephalopathy was the result of disruption of the splenic marginal zone microarchitecture, which led to reduced accumulation of the transmissible spongiform encephalopathy agent in the spleen; thereby limiting disease progression. 40 In summary, our study shows that the splenic architecture undergoes age-associated changes, which is consistent with similar observations that have been reported in rats 55,56 and humans, and suggests that such alterations might impact on immune activity and therefore contribute towards peripheral immunosenescence and may also offer a potential target for rejuvenating the immune system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…54 In contrast, it was recently demonstrated that the inability of aged mice to develop transmissible spongiform encephalopathy was the result of disruption of the splenic marginal zone microarchitecture, which led to reduced accumulation of the transmissible spongiform encephalopathy agent in the spleen; thereby limiting disease progression. 40 In summary, our study shows that the splenic architecture undergoes age-associated changes, which is consistent with similar observations that have been reported in rats 55,56 and humans, and suggests that such alterations might impact on immune activity and therefore contribute towards peripheral immunosenescence and may also offer a potential target for rejuvenating the immune system.…”
Section: Discussionsupporting
confidence: 92%
“…as detected by the expression of mucosal addressin cell adhesion molecule 1, has been shown to be less intact in the aged spleen. 39,40 Furthermore, sphingosine-1-phosphate receptor 3 deficient mice display a disorganized marginal zone region and exhibit a reduced T-independent response; 41 highlighting the importance of an intact region. Moreover, this region is not only important as the entry and exit point of leucocyte trafficking, but also the site where antigens are sequestered.…”
Section: Discussionmentioning
confidence: 99%
“…Although many of these changes were most prominent in mice ≥ 18 months old, significant disruption to the MAdCAM‐1 + MZ sinus lining cells was evident from as early as 9 months old and preceded the changes to MZ B cells observed at 12 months. Hence these data show that significant ageing‐related changes are evident in the splenic MZ much earlier than has been previously described 6, 7, 8. The timing of the changes observed also suggests that the ageing‐related disturbances to the distribution of the MAdCAM‐1 + MZ sinus lining cells may lead to subsequent disturbances to the distribution of MZ B cells and MZ metallophilic macrophages.…”
Section: Resultssupporting
confidence: 67%
“…Our laboratory has previously demonstrated this in 20‐month‐old C57BL/Dk and RIII mice,6, 7 and an independent study has reported disturbances to the MZ in C57BL/6 mice > 12 months old 9. Others have also demonstrated changes to the MZ of 17‐ to 18‐month‐old BALB/c mice 8.…”
Section: Resultsmentioning
confidence: 66%
“…Prolonging the incubation of the mice beyond this period may not provide a gain of sensitivity, as PrP res accumulation in spleen, even at the highest vCJD dilutions, could be maximal. Additionally, spleens of mice over 1.5 years of age may show impaired capacities to replicate prions, due to declines in the functions of follicular dendritic cells where PrP Sc accumulate or alteration in the microarchitecture of the germinal center where these cells are located (34,35).…”
Section: Discussionmentioning
confidence: 99%